Prescribing pattern of antipsychotics for patients with schizophrenia using the total daily dose online tool - Jawza F. Alsabhan; Haya M. Almalag; Lubna Aljafali; Hessa Alnughamish; Gaida Almutlaq (Elsevier, 2023)
This study aimed to investigate the prescribing pattern of antipsychotic medications for schizophrenia using the British National Formulary total daily dose (TDD) online tool. We analysed data from the electronic medical records at King Khalid University Hospital (KKUH) of 272 patients diagnosed with schizophrenia who were prescribed both typical and atypical antipsychotic medications. The results showed that aripiprazole was the most commonly prescribed antipsychotic drug, followed by haloperidol then risperidone. The TDD online tool was used to calculate the TDD of each prescribed antipsychotic medication. Most patients were prescribed doses within the recommended range for each medication, although some were prescribed doses above or below the recommended range. Moreover, a high recommended TDD was associated with the combined use of antipsychotics rather than monotherapy. Additionally, high TDD levels were associated with the following antipsychotics: haloperidol, olanzapine, paliperidone, and quetiapine. Our findings highlight the importance of using evidence-based tools such as the TDD online tool to guide prescribing practices and ensure optimal dosing of antipsychotic medications for patients with schizophrenia.